Decoding Speech Acts in the Hunger Games Movie - Alicia, Terresa; Nabila, Zulfa (Proceedings Series on Social Sciences & Humanities, 2025)
English proficiency plays a critical role in global communication, especially in education and entertainment. One effective method to enhance speaking and pragmatic competence is through the use of English movies. This study aims to analyze speech acts in The Hunger Games movie using the theories of J.L. Austin and John Searle. A qualitative approach was employed to identify and categorize various types of speech acts such as assertive, directive, commissive, expressive, and declarative acts. In addition to these classifications, the analysis also considers Austin’s tripartite framework of speech acts: locutionary acts (the literal meaning of utterances), illocutionary acts (the speaker’s intention), and perlocutionary acts (the effect on the listener). The findings revealed that assertive and directive acts were most dominant. This research contributes to a deeper understanding of pragmatics in cinematic dialogue and highlights how language use in movies can aid learners in developing both linguistic and sociocultural competence.